Course Learning System - O'Keefe, Tara Lynn (Course Technology, 2000)
This highly visual training manual contains six units that cover Intermediate Microsoft Excel skills. Through instructor-led or self-paced step-by-step instruction, individuals learn how to manage workbooks, automate tasks, use and analyze list data, enhance charts and worksheets, and work with Excel and the Internet. Each unit concludes with a Concept and Skills Review, World Wide Web work, and Independent Challenges providing individuals with hands-on practice of every skill they learned in the unit